Estudo e Simulação de uma Rede de Distribuição de Chaves Quânticas de Alto Desempenho para o Campus da UFPA - Tavares, David; Pimentel, Arthur; Abreu, Diego; Abelém, Antônio (Proceedings of the Regional School of High Performance North 2 (ERAD-NO2) and Regional School of Machine Learning and Artificial Intelligence North 2 (ERAMIA-NO2); 2023: Proceedings of the 3rd Regional School of High Performance North 2 and the 3rd Regional School of Machine Learning and Artificial Intelligence North 2, 2023)
This paper presents the design and simulation of a Quantum Key Distribution (QKD) network tailored for the University Federal do Pará (UFPA) campus. By strategically placing QKD nodes, the network aims to cater to the communication needs of diverse research institutes. Simulation parameters, including inter-node distances and quantum key rates, were chosen to reflect realworld conditions. Simulation results demonstrate the viability of the proposed QKD network, showcasing its potential for high demand secure key exchange, and allowing security applications such as authentication and cryptography. This endeavor not only enhances campus communication security but also sets a precedent for implementing QKD networks in similar academic settings.